Processing trade, exchange rates, and the People's Republic of China's bilateral trade balances - Yuqing Xing (Asian Development Bank Institute (ADBI), 2011)
This paper analyzes the role of processing trade in the People's Republic of China (PRC)'s bilateral trade balances and the impact of the yuan's appreciation on processing trade. The analysis is based on panel data covering the PRC' 51 trading partners from 1993 - 2008. The empirical analysis shows that: (1) processing trade accounts for 100% of the PRC's overall trade surplus and can explain most of its bilateral trade balances; (2) the PRC's processing trade shows a significant regional bias - its processing exports to East Asian economies are three times those to other regions while its processing imports from East Asian economies are eleven times those from other regions; (3) the PRC is one of the major sources of its own processing imports, accounting for 16.8% of its total processing imports from all 51 trading partners; and (4) the appreciation of the yuan would affect both processing imports and exports in the same direction - specifically, a 10% real appreciation of the yuan would reduce not only the PRC's processing exports by 9.6% but also its processing imports by 3.9%. Therefore, a moderate appreciation of the yuan would have a very limited impact on the PRC's trade balance.
Keywords: F1; 330; Handelsbilanz; Renminbi; Aufwertung; Veredelungsverkehr; Außenhandelseffekt; China